Parenting a Child with Phenylketonuria (PKU): an Interpretative Phenomenological Analysis (IPA) of the Experience of Parents - Carpenter, Katie (J Genet Couns, 2018)
Phenylketonuria (PKU) is a rare inherited metabolic disorder which can cause neurological damage if left untreated. PKU is identified through newborn screening in developed countries, and treatment begins immediately to prevent these severe consequences. When a child is diagnosed, parents must assume immediate responsibility for the management of PKU and prevention of neurological damage. Quantitative studies have identified significant psychosocial stressors for parents, but little is known about how the parents experience this process. This study aimed to explore the experiences of parents of children with PKU under the age of two. It is the first study to examine these experiences in this way. Seven parents were interviewed about their experiences, and interpretative phenomenological analysis was used to analyse the data. Three main themes were identified: control, striving for normality and acceptance of PKU as a continuum. Links between the themes and processes underpinning the results were explored with relation to existing literature and theories from a clinical psychology perspective. The role of acceptance of PKU was central to the parent’s experiences. Clinical implications and suggestions for further research are discussed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10897-018-0227-7) contains supplementary material, which is available to authorized users.